Answer:
Step-by-step explanation:
Answer:
(2,8)
Step-by-step explanation:
Add them together to get rid of the y.
-6x = -4 - y
-7x = -22 + y
=
-13x = -26
Then solve for x.
-13x/-13 = -26/-13
x = 2
Now plug in the x value into either equation and solve for y.
-7(2) = -22 + y
-14 = -22 + y
-14 + 22 = -22 + 22 + y
8 = y
So...
x = 2
y = 8
(2,8)
Search it up, you’ll get some answers. it maybe work
For this case we have the following polynomial:
To answer the question, what we must do is rewrite the polynomial in its standard form.
We have then that the polynomial will be given by:
Therefore, we have the ordered polynomial in descending form of exponents.
Therefore, the second term of the polynomial is:
Answer:
The second term of the polynomial is given by:
Answer: D, or 1+cotangent squared theta= cosecant squared theta
Step-by-step explanation: Took the test it is right